Hemodynamic Solution Computation and Pathological Analysis in the Circle of Willis - Sui, J.; Yang, L.; Zhang, Xinguang; Shi, H.; Hu, Y. (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Hemodynamic indexes will change significantly compared to the normal range of many vascular diseases, therefore it is necessary to establish hemodynamic computation model. Blood circulation is periodically forced huge fluid flow network, the heart is generator of the entire fluid network, based on this hemodynamic characteristics, the circle of Willis’s structure is simplified from the perspective of network and hemodynamics. According to hemodynamic equations and circuit graph theory, models blood flow network of the periodically forced hemodynamic equation, obtains the approximate solution of the harmonic waves form based on averaging computation. We apply this model in the network of the circle of Willis, which may help explain the development processes of cerebral circulation disease. The simulation results show that computing results consistent with the clinical observation of blood flow changes in cerebral infarction.